Inventory of Orchids in Some Area of Manusela National Park-Maluku - Tirta, IG. (Proceeding International Conference on Global Resource Conservation, 2013)
Manusela National Park as one of the conservation areas in Indonesia with 189.000 Ha, located in the central part of the island of Seram, Central Maluku Regency, Maluku Province. Maluku Province has different characteristics compared to other protected areas. Information on the kind of orchid flora is limited. Base of mentioned above the research were conducted in Manusela National Park (Taman Nasional Manusela).The aim of this research are to inventory and collect the orchid at MNP. The research was done in 17 days from May 24 to June 9, 2011 with exploration method. Results shows that 73 species were found and collected. Most of the collection are Dendrobium genus (13 of species). Key words : Inventory, Manusela National Park, orchid